Suggestions from the field for return to sports participation following anterior cruciate ligament reconstruction: American Football - Verstegen, M.; Falsone, S.; Orr, R.; Smith, S. (Journal of Orthopaedic & Sports Physical Therapy, 2012)
Returning an American football player to sport after an anterior cruciate ligament reconstruction is challenging on several fronts. First, there are approximately 15 different positions a football player could play, depending on how specifically you define the positions on the field. Each of these positions has specific demands for optimal size, strength, power, body composition, cardiovascular fitness, and movement. Understanding all of these factors is paramount to returning a football player not only to his sport but also to his specific position. Second, the chaotic, contact-rich nature of the sport requires that heavy demands be placed on the lower extremities to attenuate external contact forces from other players and from ground reaction forces associated with accelerating, decelerating, quick stops and starts, and changing direction. Finally, return to a competitive level of performance is further influenced by playing surface, shoe selection, the equipment the player wears, and various potential psychosocial factors. It is the responsibility of the clinician to provide a progressive and systematic rehabilitation program by first introducing preprogrammed movements that, once mastered, are progressed with elements of more reactive and random movement patterns. The precise nature of this systematic progression of advanced rehabilitation is key in developing return-to-play criteria and, ultimately, in readying an American football player for eventual return to sport and a particular position.